Redescriptions of Spinitectus acipenseri and S. micracanthus (Nematoda, Cystidicolidae), with notes on the taxonomy of Spinitectus-like nematodes parasitising North American fishes - Moravec, František; Huffman, David G; de Buron, Isaure; González-Solís, David (Parasite (Paris, France), 2023)
Based on light microscopical and scanning electron microscopical (SEM) examinations, two North American species of Spinitectus Fourment, 1884, S. acipenseri Choudhury & Dick, 1992 and S. micracanthus Christian, 1972 (Nematoda, Cystidicolidae) are redescribed from museum voucher specimens (S. acipenseri) and those newly collected from centrarchid and some other fishes in the Upper San Marcos River in Texas and the Santee River in South Carolina, USA. The first use of SEM to study S. acipenseri, a parasite of lake sturgeon Acipenser fulvescens Rafinesque (Acipenseridae) in Canada, made it possible to describe dorsal and ventral lips, amphids and sublabia, and the presence of a dorsal barb on the right spicule, which was confirmed to be the most characteristic feature of this species. The SEM study of S. micracanthus, a parasite mainly of centrarchids, enabled us to correctly determine the location of the excretory pore in relation to rings of cuticular spines in the male, and to describe the exact structure of the tip of the male tail, sublabia, phasmids and the presence of a median ventral protuberance on the male tail. Some taxonomic problems of North American species of Spinitectus are discussed. Filaria serrata Linton, 1901 is considered a junior synonym of S. oviflagellis Fourment, 1884. To date, there are 13 valid species of Spinitectus parasitising fishes in North America. Keys to species of Spinitectus-like nematodes from fishes in North American waters are provided.
Keywords: Canada; Fishes; Spiruroidea; Gastropoda; plži; North America; ryby; Ctenascarophis; Microscopy, Electron, Scanning; Severní Amerika; Parasitic nematode; Prospinitectus; mužské pohlaví; South Carolina; zvířata; USA; Texas; Animals; Male; mikroskopie elektronová rastrovací; Morphology